Exploring The Teachers' Identity in Sakae Tsuboi's Twenty-Four Eyes - Sanjaya, Paschalis Kurniawan; Bram, Barli (Jetlal, 2025)
Teachers play an essential role in the field of education. Their identities are crucial to the teaching profession. In the wide range of literary works, especially books or novels, teachers often appear as a character. This research was conducted to explore the identity of the teacher depicted in Japan's legendary novel Twenty-Four Eyes by Sakae Tsuboi which was translated by Akira Miura. This novel tells the story of a young teacher's journey in a remote area of Japan during World War II. One research question was raised, “how is the teacher identity depicted in the Sakae Tsuboi: Twenty-Four Eyes?” Qualitative research, specifically document analysis was used to explore the teacher identity in this novel. The researchers also implemented a close reading method to gain a deeper understanding about the related topic. The data was carefully analyzed using thematic analysis. The use of a Social Role Theory (SRT) helps the researchers to interpret the text. It showed that social relations happening will affect feelings, thoughts, and behaviors. Based on the text, the researchers concluded three themes appeared as the identity from the teacher; teacher as an educator, as an inspirator, as a challenger, and as oppressed. It is hoped that through the result of the research, teachers, educators, or even scholars can gain meaningful insight related to identity.